Prevalence of occupational health problems and safety measures among workers of cement factory. - Sharma, Yashmina (2009)
ABSTRACT: This descriptive study entitled "Prevalence of Occupational Health Problems and Safety Measures among the Workers of Cement Factory" was carried out as a partial fulfillment of the Degree of Bachelor of Science in Nursing. The objective of the study was to find out the prevalence of occupational health problems and safety measures among the workers of the cement factory. The study was carried out in Butwal Cement Factory of Nawalparasi District. The factory was selected by using non-probability purposive sampling and the total 98 workers working in the factory were studied. Semi-structured interview questionnaire was used to collect the data. The obtained data was analyzed by using descriptive statistics. Study findings revealed that there were 100 percent male workers working in the factory. Majority of workers were literate (70.4%) and only 29.6% were illiterates. Among them 56% were facing health problems on which 20.4% had shortness of breath, 19.3% had skin diseases, 11.2% had prolonged cough and 13.2% had eye disease & ear disease respectively. Regarding the safety measures, 60.2% workers were using masks, 33.7% using gloves, 30.6% using caps, 8.2% using goggles and 5.1% using boots and belts regularly. Regarding the availability of facilities, quarters and canteens were most evident. All the workers for 12 hours daily. The maximum duration of workers working in the factory was 12 years. The conditions of housekeeping, safe drinking water and dust control measures of the working place were good. There was no provision of sick leave, periodic medical examination and regular supervision of the workers. The conditions of the infrastructure and building, ventilation, canteen and toilet were miserable . So, it was concluded that factory management was poor in establishing the sound environment for the workers. Thus it was recommended that the management should focus on providing safe working environment for them.